2018
DOI: 10.1093/europace/euy267
|View full text |Cite
|
Sign up to set email alerts
|

Survival after cardiac resynchronization therapy: results from 50 084 implantations

Abstract: Aims Randomized controlled trials have shown that cardiac resynchronization therapy (CRT) prolongs survival in patients with heart failure. No studies have explored survival after CRT in relation to individuals in the general population (relative survival, RS). We sought to determine observed and RS after CRT in a nationwide cohort undergoing CRT. Methods and results A national administrative database was used to quantify observed mortality for patients undergoing CRT. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
25
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 19 publications
6
25
0
2
Order By: Relevance
“…Female gender has been associated with a “super‐response” to CRT in previous studies, thus women are also more likely to be offered a CRT‐P in NZ . This trend is consistent with several contemporary international registries and studies . Of note, those studies have shown very similar LV systolic function between the CRT‐P and CRT‐D cohorts, with CRT‐P having a longer mean QRS duration.…”
Section: Discussionsupporting
confidence: 83%
“…Female gender has been associated with a “super‐response” to CRT in previous studies, thus women are also more likely to be offered a CRT‐P in NZ . This trend is consistent with several contemporary international registries and studies . Of note, those studies have shown very similar LV systolic function between the CRT‐P and CRT‐D cohorts, with CRT‐P having a longer mean QRS duration.…”
Section: Discussionsupporting
confidence: 83%
“…The most recent clinical trials led by Francisco [5] and Jian-Shu [34] found that ischemic cardiomyopathy is a significant predictor related to worse survival after the CRT. The underlying mechanism of this phenomenon could be explained by CRT correcting conduction disorders caused by delayed activation regions of the left ventricular wall.…”
Section: Discussionmentioning
confidence: 99%
“…The main factors associated with HF prognosis are male gender; age; elevated resting heart rate; hospital admissions and emergency department visits the previous year; natriuretic peptides; troponin T and I levels; and comorbidities: diabetes mellitus, chronic kidney disease, dementia, cirrhosis, atrial fibrillation, cardiac conduction disorders, ischemic origin of HF, hypertensive heart disease, etc. [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Comorbidities are frequent in heart failure and affect the delivery and effect of heart failure therapy, functional status, and clinical outcomes 77–80 . Due to this competing risk patients with comorbidities derive less benefit from an ICD (see next section).…”
Section: Action Plan For Referral and Optimization Of Cardiac Resynchmentioning
confidence: 99%